Distinct roles of the anterior cingulate and prefrontal cortex in the acquisition and performance of a cognitive skill - Fincham, Jon M. (National Academy of Sciences, 2006)
The purpose of the present work is to study the functional roles of two predefined regions of interest: one in the left anterior cingulate cortex (ACC) that seems to reflect goal-relevant control demand, and one in the left prefrontal cortex (PFC) that reflects memory retrieval demand. Two slow event-related brain imaging experiments were conducted, adapting a cognitive skill acquisition paradigm. Experiment 1 found that both left ACC and left PFC activity increased parametrically with task difficulty. Using a slight modification of the same basic paradigm, Experiment 2 attempted to decouple retrieval and control demands over the course of learning. Participants were imaged early in training and again several days later, after substantial additional training in the task. There was a clear dissociation between activity in the left PFC and the left ACC. Although the PFC region showed a substantial decrease in activity over the course of learning, reflecting greater ease of retrieval, the ACC showed the opposite pattern of results with significantly greater activity after training, reflecting increased control demand. Moreover, the increased response in the ACC occurred when errors and latencies were smallest.